Given:
color(white)("XXX")y=4-x^2+3x
Re-arrange the equation to solve for x in terms of y
color(white)("XXX")-y=x^2-3x-4
color(white)("XXX")-y= (x^2-3xcolor(red)(+(3/2)^2))-4color(red)(-9/4)
color(white)("XXX")-y=(x-3/2)^2-25/4
color(white)("XXX")(x-3/2)^2=25/4-y
color(white)("XXX")x-3/2=+-sqrt(25-4y)/2
color(white)("XXX")x=(3+-sqrt(25-4y))/2
In order to maintain y as the dependent variable (and x as the independent variable) it is common to exchange the x and y variables at this point.
In this case the inverse would be written as:
color(white)("XXX")y=(3+-sqrt(25-x))/2
Sometimes the y is written in some modified form such as y' to avoid confusing it with the y in the original equation.
Check with your instructor for the form she/he wants you to use.